Ectopic thyroid microfollicular adenoma in the lung: A case report. Issue 35 (August 2019) - Zhang, Wenjun; Zhang, Hongsheng; Hou, Qiaoru; Hou, Hongjun; Xu, Dong; Liu, Jie; Shi, Lu
Abstract: Introduction: Ectopic thyroid occurs due to aberrant development of the thyroid gland during its migration to the pretracheal region. Intrapulmonary ectopic thyroid is extremely rare and its benign transformation (microfollicular adenoma) has never been reported. This paper reports a case of ectopic thyroid microfollicular adenoma in the lung mimicking metastatic pelvic tumors. Patient concerns: A 76-year old female presented to our hospital because of transient unconsciousness. Pelvic ultrasound (US) and chest computed tomography (CT) showed pelvic tumors and pulmonary nodules. Diagnosis and interventions: The patient underwent pelvic tumors resection and CT-guided fine-needle aspiration cytology (FNAC) at the largest pulmonary nodule. Pathological description revealed bilateral ovarian serous cystadenoma and endometrioma in pelvic, and ectopic thyroid microfollicular adenoma in lung. In view of the patient's age and physical conditions, it is unanimously decided by the physicians and the family members of the patient to closely follow up this benign pulmonary lesion. Outcomes: During the 12-month follow-up, no pelvic tumor recurrence or metastasis was found. CT review of pulmonary nodules showed no remarkable changes. The patient was asymptomatic and euthyroid after being discharged from the hospital. Conclusion: Ectopic thyroid microfollicular adenoma in the lung is extremely rare and can be easily mistaken for pulmonary metastases from other sites. The case reported in this paper highlights that ectopic intrapulmonary thyroid tumor should not be overlooked.